An effective library website: a data-driven approach to its management using analytical tools - О. M. Udartseva (Библиосфера)
This article is devoted to topical issues of increasing the efficiency ofa library website and the introduction of a data-driven approach. A data driven approach is considered as a management strategy for the development of a site in a web environment, based on data from web analytical tools as the basis for decision-making. The author has developed a website management model that includes the sequence of actions: goal setting, performance monitoring, data analysis, planning, decision-making, implementation of changes, control. The proposed management model allows one the application of a unified approach and management tools to a library website, depending on the goals set, identify current problems and, on the basis of objective decisions, develop its further development strategy in the information environment. The article presents the results of approbation of the model on the example of website management of the State Public Scientific Technological of the Siberian Brach of the Russian Academy of Sciences and notes the advantages of managing a library website based on a data-driven approach.